Introduction to aircraft structural analysis - Megson, T. H. G. (Butterworth-Heinemann, 2017)
Introduction to Aircraft Structure Analysis, Third Edition covers the basics of structural analysis as applied to aircraft structures. Coverage of elasticity, energy methods and virtual work set the stage for discussions of airworthiness/airframe loads and stress analysis of aircraft components. Numerous worked examples, illustrations and sample problems show how to apply the concepts to realistic situations. As a self-contained guide, this value-priced book is an excellent resource for anyone learning the subject.